Resilience in standardized housing estates: Housing monotony and adjustments - Fashuyi, Olugbenga; Osman, Amira (Edelweiss Applied Science and Technology, 2025)
This study examines users’ housing adjustments in standardized housing estates. It observed that housing adjustments in the estates are an expression of users’ resilience and a response to the monotony of standardized housing. To gain insight into the users’ resilience, the study developed a conceptual framework that highlighted housing adjustment and resilience indicators. The research method is qualitative, and it employs a schedule for in-depth interviews while the content analysis of the interview transcripts was achieved through the DocTool software. The study showed that residents of the estates are grouped into teams of expertise linked to their life cycle stages for the reconstructions required in their house adjustments. Moreover, community housing norms in the estates are developed from new layers of knowledge derived from housing adjustments and the reconstructions they involve. The study also linked residents’ perceptions and gestalt to their resilience and housing adjustments. A significant achievement of the study is developing a conceptual framework for housing adjustment studies.